2002
DOI: 10.1086/342765
|View full text |Cite
|
Sign up to set email alerts
|

The Planetary Nebula Spectrograph: The Green Light for Galaxy Kinematics

Abstract: Planetary nebulae are now well established as probes of galaxy dynamics and as standard candles in distance determinations. Motivated by the need to improve the efficiency of planetary nebulae searches and the speed with which their radial velocities are determined, a dedicated instrument -the Planetary 1 Currently at California Institute of Technology, Pasadena, USA Nebulae Spectrograph or PN.S -has been designed and commissioned at the 4.2m William Herschel Telescope. The high optical efficiency of the spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 32 publications
3
79
0
1
Order By: Relevance
“…This has been possible thanks to dedicated observational campaigns and instrumentation (such as the PN.Spectrograph, Douglas et al 2002). Observations of PNe probe the photometric and kinematic profiles of the starlight well beyond the effective radius, where the surface-brightness would be too low ).…”
Section: Introductionmentioning
confidence: 99%
“…This has been possible thanks to dedicated observational campaigns and instrumentation (such as the PN.Spectrograph, Douglas et al 2002). Observations of PNe probe the photometric and kinematic profiles of the starlight well beyond the effective radius, where the surface-brightness would be too low ).…”
Section: Introductionmentioning
confidence: 99%
“…The PN Spectrograph (PN.S) is an instrument on the William Herschel Telescope dedicated to measuring PN velocities in nearby galaxies (Douglas et al 2002). The pupil is split in half before being dispersed in opposite directions in twin spectrographs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, clues on angular momentum alignment could change when looking at the halo regions of these systems. Preliminary results on PNe radial velocity fields of NGC 3379 and NGC 4494 from the Planetary Nebula Spectrograph, (PN.S, Douglas et al 2002), have revealed that there is a tilt of the major kinematical axis of the PNe sample with respect to the stellar long-slit data as it is clearly shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 87%